High-strength and weather-resistant bridge section assembling adhesive and preparation method thereof

By using a high-strength, weather-resistant bridge segment assembly glue composed of component A and component B with a mass ratio of 2:1, organic titanium modified epoxy resin and amine curing agent are used, combined with titanate The bridging effect of the coupling agent and the silane coupling agent forms chemical bonds and a laminated structure, which solves the problem of the degradation of bridge segment assembly glue in harsh environments in the existing technology, and achieves high strength and weather resistance.

CN119331552APending Publication Date: 2025-01-21SHANDONG NORTH MODERN CHEM IND
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411513841.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When the existing bridge segment assembly glue is used in harsh environments such as high temperature and high humidity, the service performance of the glue joints will deteriorate, resulting in the impact of the structural reliability and durability.

Method used

A high-strength, weather-resistant bridge segment assembly adhesive composed of component A and component B with a mass ratio of 2:1. Component A is composed of organic titanium modified epoxy resin, phenolic modified epoxy resin, and Kistzen Toughening agent, etc., component B consists of amine solids It is composed of chemical agent, silane coupling agent, etc. Through the bridging effect of titanate coupling agent and silane coupling agent, the adhesive layer and the adherend are chemically bonded to enhance the bonding strength, and a laminated structure is formed through glass flakes. Improve waterproof performance.

Benefits of technology

It achieves good bonding strength in complex and changeable external environments, significantly improves the durability and reliability of the bridge segment assembly structure, and is suitable for large-scale bridge segment assembly projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331552A_ABST
    Figure CN119331552A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and weather-resistant bridge section assembling adhesive and a preparation method thereof, and relates to the technical field of assembling adhesives and sealing bonding materials, the high-strength and weather-resistant bridge section assembling adhesive is composed of a component A and a component B in a mass ratio of 2: 1; the component A is prepared from organic titanium modified epoxy resin, phenolic aldehyde modified epoxy resin, a Qishi toughening agent, a phthalic ester coupling agent and other raw materials; the component B is prepared from the following raw materials: an amine curing agent, a curing accelerator, a silane coupling agent, quartz powder and the like; the high-strength and weather-resistant bridge section assembling glue is long in operable time, rapid in strength increase, wide in construction environment temperature range and convenient to construct. A curing system adopts a low-molecular polyamide and modified aromatic amine compound curing agent system, the compound curing agent enables the adhesive to have better constructability within one hour, and the adhesive can quickly form strength after construction, has high condensate compression strength and elasticity modulus, is wider in construction environment temperature range, and is convenient to construct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of assembling glue and sealing adhesive materials, in particular to a high-strength and weather-resistant bridge segment assembling glue and a preparation method thereof. Background Art

[0002] The prefabricated segment assembly technology combines the technical theories of prestressed structure and segmented construction method, and divides the overall bridge structure into several segments. After each segment is prefabricated by short-line or long-line matching method, it is transported to the designated location for assembly and prestressed to ensure the stability of the overall structure. Epoxy resin bonding materials are used in the connection between segments, and the bonding force of epoxy resin glue is used to tightly connect adjacent segments together. This connection method not only has good sealing performance, but also has short construction time, high engineering quality, and little impact on the environment, so it has broad application prospects.

[0003] There are obvious differences between the prefabricated segmental adhesive joint assembly structure and the integral cast structure. The longitudinal ordinary steel bars and concrete are discontinuous at the segmental assembly joints. The joints between the segments are filled with adhesives. The force transmission of the overall structure depends on the performance of the joints between the segments. The performance of the joints between the segments directly affects the reliability of the assembled structure and the safety quality of the project. As the weakest part of the assembled structure, the prefabricated segment joints are also the most susceptible to damage and destruction, which gradually extends to the destruction of the overall structure. Therefore, improving the durability of prefabricated concrete segment joints has also become the key to the safety and durability of prefabricated segmental structure projects.

[0004] The service life of bonded components is not only affected by the durability of the adhesive itself, but also closely related to the structure of the bonding interface and the application environment. The temperature, humidity, chemical media and stress of the environment can all produce physical or chemical changes through the interface effect, causing reversible and irreversible changes at the bonded joints, thereby changing the stress state of the bonded joints and affecting the durability of the structure. As a key bonding material for new joint technologies used in industrialized construction, many domestic and foreign scholars have verified its applicability in prefabricated segment assembly projects through experimental research. However, when splicing adhesives are used in harsh engineering environments such as coastal areas, high temperature, and high humidity, the service performance of the bonded joints will deteriorate under the long-term action of natural environments and complex stresses, and may even fail or be damaged, seriously affecting the reliability and durability of the structure.

[0005] Therefore, there is an urgent need to develop a bridge segment splicing adhesive that can cope with the erosion of the complex and changeable external environment and still maintain good bonding strength. Summary of the invention

[0006] To solve the above problems, the purpose of the present invention is to provide a high-strength, weather-resistant bridge segment assembly adhesive and a preparation method thereof to meet the demand for high-performance assembly adhesive in bridge prefabrication assembly technology.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0008] A high-strength, weather-resistant bridge segment assembly adhesive, composed of a component A and a component B in a mass ratio of 2:1; in parts by weight, the component A is composed of the following raw materials: 8-12 parts of an organic titanium-modified epoxy resin, 8-12 parts of a phenolic-modified epoxy resin, 3-4 parts of a Qishi toughening agent, 0.5-1 part of a phthalate coupling agent, 20-30 parts of a first quartz powder, 10-20 parts of a first glass flake, and 2-4 parts of a first thixotropic agent; the component B is composed of the following raw materials: 5-10 parts of an amine curing agent, 0.1-0.5 parts of a curing accelerator, 0.1-0.5 parts of a silane coupling agent, 8-15 parts of a second quartz powder, 8-15 parts of a second glass flake, 1-2 parts of a second thixotropic agent, and 0.001 parts of iron chrome black;

[0009] The epoxy equivalent of the organic titanium modified epoxy resin is 312 to 333 g / eq;

[0010] The epoxy equivalent of the phenolic modified epoxy resin is 160 to 170 g / eq.

[0011] Preferably, the organic titanium modified epoxy resin is prepared according to the following steps:

[0012] Add epoxy resin E-51 into a reaction kettle, start stirring and heat to 130-140°C, add tetrabutyl titanate dropwise while stirring, keep warm and react for 2-3 hours after the addition is complete, remove by-products and low-boiling substances by distillation under reduced pressure, and obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 312-333 g / eq;

[0013] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 185-206:26-28.

[0014] Preferably, the viscosity of the Qishi toughening agent is 50 to 500 mPa·S.

[0015] Titanate coupling agents that can be used in the present invention include NDZ-109, TM-3, NDZ-401, NDZ-201, etc., and silane coupling agents that can be used in the present invention include KH-602, KH-792, A-151, A-1160, etc. Preferably, the titanate coupling agent is NDZ-201; the silane coupling agent is A-1160. The preferred solution is to achieve chemical bonding between the adhesive layer and the adherend through the bridging effect of the titanate coupling agent and the silane coupling agent, and the bonding strength is greatly increased. At the same time, the siloxane polymer on the interface is a hydrophobic film that covers the surface of the substrate and can effectively prevent the penetration and diffusion of moisture. In other words, a complete waterproof interface is formed, which plays a protective role. The adhesive has excellent weather resistance after curing due to the synergistic effect of low water absorption organic titanium modified epoxy resin, phenolic modified epoxy resin as the main resin polyamide, modified aromatic amine as the curing agent, titanate coupling agent, silane coupling agent, fumed silica and pigment iron chrome black.

[0016] Preferably, the amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 3-5:5-7.

[0017] Preferably, the first thixotropic agent is hydrophobic fumed silica whose surface is treated with a titanate coupling agent; and the second thixotropic agent is polyamide wax.

[0018] The present invention also includes a method for preparing a high-strength, weather-resistant bridge segment assembly adhesive, comprising the following steps:

[0019] ① Preparation of component A: In parts by weight, add 8-12 parts of organic titanium modified epoxy resin, 8-12 parts of phenolic modified epoxy resin, 3-4 parts of Qishi toughening agent, and 0.5-1 part of phthalate coupling agent to the first planetary mixer, mix evenly, add 2-4 parts of the first thixotropic agent thereto and continue stirring for 15-20 minutes, add 20-30 parts of the first quartz powder and 10-20 parts of the first glass flakes thereto after mixing evenly, continue stirring for 80-100 minutes, and after mixing evenly, evacuate the materials in the first planetary mixer to remove bubbles, package and store to obtain component A, which is a white paste;

[0020] The epoxy equivalent of the organic titanium modified epoxy resin is 312 to 333 g / eq;

[0021] The epoxy equivalent of the phenolic modified epoxy resin is 160 to 170 g / eq;

[0022] ② Preparation of component B: Add 5-10 parts of amine curing agent, 0.1-0.5 parts of curing accelerator, and 0.1-0.5 parts of silane coupling agent to the second planetary mixer, stir and mix, add 8-15 parts of second quartz powder, 8-15 parts of second glass flakes, 1-2 parts of second thixotropic agent and 0.001 parts of iron chrome black, continue to mix and stir for 80-100 minutes, after mixing evenly, evacuate the materials in the second planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste;

[0023] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] The high-strength, weather-resistant bridge segment assembly adhesive of the present invention has high mechanical strength, good toughness, strong impact resistance and fatigue resistance, and high elastic modulus, and can significantly improve the quality and weather resistance of bridge segment assembly construction, and is particularly suitable for large-scale bridge segment assembly projects that have high requirements for the mechanical properties and weather resistance of the assembly adhesive. The present invention uses organic titanium modified epoxy resin and phenolic modified epoxy resin as the main resin, a polyamide and aromatic amine compound curing system, and a Qishi toughening agent as the toughening system. The Qishi toughening agent is a mixture of polymers with different active end groups that connect different types of chain segments. When the Qishi toughening agent is added to the epoxy system, the toughening agent aggregates into spherical particles and becomes a dispersed phase in the continuous phase composed of the epoxy resin cross-linking network, forming an island structure, which improves the toughness of the material without reducing the heat resistance of the material.

[0026] The high-strength, weather-resistant bridge segment assembly adhesive of the present invention has a long operating time, fast strength growth, a wide range of construction environment temperature, and is easy to construct. The curing system of the present invention adopts a low-molecular polyamide and modified aromatic amine compound curing agent system. The compound curing agent enables the adhesive to have good workability within one hour, and can quickly form strength after construction. The cured product has high compression strength and elastic modulus; the compression strength is greater than 60MPa in 24h and greater than 80MPa in 7 days. Curing can also be completed in a low temperature environment under the action of an accelerator, and the construction environment temperature is relatively wide in the range of 5 to 35°C, which is convenient for construction.

[0027] The high-strength, weather-resistant bridge segment assembly adhesive of the present invention has high bonding interface strength with segment beams and good weather resistance. The organic titanium modified epoxy resin of the present invention is prepared by dealcoholization reaction between organic titanium and hydroxyl groups in epoxy resin. Before modification, epoxy resin contains hydroxyl groups, which are water-absorbing groups and easily absorb moisture, and are often the main reason for the increase in water absorption, poor moisture resistance and aging resistance of epoxy resin after curing; the introduction of the metal element titanium into epoxy resin not only solves the problem of increased water absorption, reduced moisture resistance and resistance to wet heat due to the presence of hydroxyl groups, but also because the oxygen atoms with p electrons and the titanium atoms with d electron vacancies in the resin are directly connected, so that there is a pd conjugation effect in the macromolecular chain, which significantly improves its heat aging resistance. The organic titanium modified epoxy resin replaces the hydroxyl group with titanyl, which improves the moisture resistance, heat resistance and aging resistance of the epoxy resin. On the other hand, glass flakes have a thin sheet-like configuration, and after combining with the base material (organic titanium modified epoxy resin and phenolic modified epoxy resin), they form a stacked structure in the adhesive layer, which has a great isolation effect and can shield and inhibit the migration and penetration of water, water vapor, and oxygen, thereby improving the density of the adhesive layer and greatly improving the anti-corrosion effect of the cured adhesive layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram of the state of the high-strength, weather-resistant bridge segment assembly adhesive component A and component B after mixing. DETAILED DESCRIPTION

[0029] The object of the present invention is to provide a high-strength, weather-resistant bridge segment assembly adhesive and a preparation method thereof. The present invention is further described below in conjunction with specific embodiments.

[0030] The amine curing agent aromatic amine condensate 105 of the present invention is provided by Changsha Chemical Research Institute and is a liquid amine curing amine with a viscosity of 500-1000 mPa·s and an amine value of 600-800 mgKOH / g.

[0031] Polyamide WSCM-4126 was provided by Zhejiang Wansheng Co., Ltd., and the amine value was 275-360 mgKOH / g.

[0032] The particle size range of the quartz powder used in the present invention is 200-400 mesh; the thickness range of the glass flakes is 2-5 microns, and the flake diameter is 325 mesh. In the process of forming the bridge segment assembly glue, due to the staggered arrangement of the glass flakes in the glue layer, the glue layer forms a unique "maze-like" shielding structure, which makes the path for the external corrosive medium to penetrate into the glue layer become tortuous, effectively prolonging the penetration time, and greatly improving the anti-permeability and protection life of the glue layer.

[0033] The Qishi toughening agent used in the present invention is produced by Beijing Jindao Qishi Material Technology Co., Ltd., and can be selected from QS-BE with a viscosity of 400-500mPa·S, QS-BC with a viscosity of 50-90mPa·S, QS-EC with a viscosity of 100-200mPa·S, or a mixture of several thereof.

[0034] The phenolic modified epoxy resin in the embodiment of the present invention is SNE-625L solvent-free phenolic epoxy resin produced by Hunan Servi New Material Technology Co., Ltd., with an epoxy equivalent of 160-170 g / eq and a viscosity of 3000-8000 mPa·S at 25°C.

[0035] The hydrophobic fumed silica whose surface is treated with a titanate coupling agent is prepared according to the following steps:

[0036] First, weigh the nano-silica and place it in an oven to dry for 20 to 24 hours. Then, add the titanate coupling agent NDZ-201 solution into a three-necked flask equipped with a condensation reflux device, turn on the ultrasonic oscillation and stir evenly, heat to 110 to 115°C and keep it warm for 2 hours to reflux. After the reaction is completed, filter, wash and dry under reduced pressure in a vacuum oven to finally obtain the modified nano-silica.

[0037] The mass ratio of nano-silicon dioxide and titanate coupling agent NDZ-201 solution is 1:5-6;

[0038] The titanate coupling agent NDZ-201 solution is a NDZ-201 toluene solution with a mass concentration of 1 to 2%.

[0039] Example 1

[0040] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 8kg of organic titanium modified epoxy resin, 8kg of phenolic modified epoxy resin, 3kg of Qishi toughening agent, 0.5kg of phthalate coupling agent NDZ-109, 20kg of quartz powder, 10kg of glass flakes and 2kg of thixotropic agent (hydrophobic fumed silica with the surface treated by titanate coupling agent); the component B consists of the following raw materials: 5kg of amine curing agent, 0.1kg of curing accelerator, 0.1kg of silane coupling agent KH-792, 8kg of quartz powder, 8kg of glass flakes, 1kg of polyamide wax thixotropic agent and 0.001kg of iron chrome black;

[0041] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B with a mass ratio of 2:1;

[0042] The organic titanium modified epoxy resin is prepared according to the following steps:

[0043] Epoxy resin E-51 was added into the reaction kettle, and the mixture was heated to 130°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 3 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 312 g / eq.

[0044] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 185:26;

[0045] The epoxy equivalent of the phenolic modified epoxy resin is 160 g / eq; the amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 3:5.

[0046] Example 2

[0047] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 12 kg of organic titanium modified epoxy resin, 12 kg of phenolic modified epoxy resin, 4 kg of Qishi toughening agent, 1 kg of phthalate coupling agent TM-3, 30 kg of quartz powder, 20 kg of glass flakes and 4 kg of thixotropic agent (hydrophobic fumed silica whose surface is treated with titanate coupling agent); the component B consists of the following raw materials: 10 kg of amine curing agent, 0.5 kg of curing accelerator, 0.5 kg of silane coupling agent KH-602, 15 kg of quartz powder, 15 kg of glass flakes, 2 kg of thixotropic agent polyamide wax and 0.001 kg of iron chrome black;

[0048] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B with a mass ratio of 2:1;

[0049] The organic titanium modified epoxy resin is prepared according to the following steps:

[0050] Epoxy resin E-51 was added into the reaction kettle, and the mixture was heated to 140°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 2 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 333 g / eq.

[0051] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 206:28;

[0052] The epoxy equivalent of the phenolic modified epoxy resin is 170 g / eq;

[0053] The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 5:7.

[0054] Example 3

[0055] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 9 kg of organic titanium modified epoxy resin, 11 kg of phenolic modified epoxy resin, 3.2 kg of Qishi toughening agent, 0.6 kg of phthalate coupling agent NDZ-201, 22 kg of quartz powder, 15 kg of glass flakes, and 2.5 kg of thixotropic agent (hydrophobic fumed silica whose surface is treated with titanate coupling agent); the component B consists of the following raw materials: 6 kg of amine curing agent, 0.2 kg of curing accelerator, 0.4 kg of silane coupling agent A-1160, 9 kg of quartz powder, 10 kg of glass flakes, 1.4 kg of thixotropic agent polyamide wax, and 0.001 kg of iron chrome black;

[0056] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B with a mass ratio of 2:1;

[0057] The organic titanium modified epoxy resin is prepared according to the following steps:

[0058] Epoxy resin E-51 was added to the reaction kettle, and the mixture was heated to 132°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 2.5 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 315 g / eq.

[0059] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 188:26.4;

[0060] The epoxy equivalent of the phenolic modified epoxy resin is 162 g / eq;

[0061] The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 4:6.

[0062] Example 4

[0063] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 10 kg of organic titanium modified epoxy resin, 10 kg of phenolic modified epoxy resin, 3.6 kg of Qishi toughening agent, 0.9 kg of phthalate coupling agent NDZ-201, 28 kg of quartz powder, 18 kg of glass flakes, and 3.8 kg of thixotropic agent (hydrophobic fumed silica whose surface is treated with titanate coupling agent); the component B consists of the following raw materials: 9 kg of amine curing agent, 0.4 kg of curing accelerator, 0.2 kg of silane coupling agent A-1160, 11 kg of quartz powder, 9 kg of glass flakes, 1.2 kg of thixotropic agent polyamide wax, and 0.001 kg of iron chrome black;

[0064] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B in a mass ratio of 2:1;

[0065] The organic titanium modified epoxy resin is prepared according to the following steps:

[0066] Epoxy resin E-51 was added into the reaction kettle, and the mixture was heated to 135°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 2 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 320 g / eq.

[0067] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 190:25;

[0068] The epoxy equivalent of the phenolic modified epoxy resin is 164 g / eq;

[0069] The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 3.5:7.

[0070] Example 5

[0071] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 11 kg of organic titanium modified epoxy resin, 9 kg of phenolic modified epoxy resin, 3.4 kg of Qishi toughening agent, 0.9 kg of phthalate coupling agent NDZ-201, 24 kg of quartz powder, 16 kg of glass flakes, and 2.8 kg of thixotropic agent (hydrophobic fumed silica whose surface is treated with titanate coupling agent); the component B consists of the following raw materials: 7 kg of amine curing agent, 0.4 kg of curing accelerator, 0.3 kg of silane coupling agent A-1160, 9 kg of quartz powder, 14 kg of glass flakes, 1.5 kg of thixotropic agent polyamide wax, and 0.001 kg of iron chrome black;

[0072] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B in a mass ratio of 2:1;

[0073] The organic titanium modified epoxy resin is prepared according to the following steps:

[0074] Epoxy resin E-51 was added into the reaction kettle, and the mixture was heated to 138°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 2.2 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 318 g / eq.

[0075] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 200:27;

[0076] The epoxy equivalent of the phenolic modified epoxy resin is 168 g / eq;

[0077] The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 4:5.

[0078] Example 6

[0079] A high-strength, weather-resistant bridge segment assembly adhesive, consisting of component A and component B; the component A consists of the following raw materials: 10 kg of organic titanium modified epoxy resin, 10 kg of phenolic modified epoxy resin, 3.5 kg of Qishi toughening agent, 0.8 kg of phthalate coupling agent NDZ-201, 25 kg of quartz powder, 15 kg of glass flakes and 3 kg of thixotropic agent (hydrophobic fumed silica with the surface treated by titanate coupling agent); the component B consists of the following raw materials: 8 kg of amine curing agent, 0.3 kg of curing accelerator, 0.3 kg of silane coupling agent A-1160, 12 kg of quartz powder, 12 kg of glass flakes, 1.5 kg of thixotropic agent polyamide wax and 0.001 kg of iron chrome black;

[0080] When in use, the high-strength, weather-resistant bridge segment assembly adhesive is composed of component A and component B with a mass ratio of 2:1;

[0081] The organic titanium modified epoxy resin is prepared according to the following steps:

[0082] Epoxy resin E-51 was added into the reaction kettle, and the mixture was heated to 135°C with stirring. Tetrabutyl titanate was added dropwise while stirring. After the addition was completed, the mixture was kept warm for 2.5 hours. Byproducts and low-boiling substances were removed by distillation under reduced pressure to obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 320 g / eq.

[0083] The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 205:27.5;

[0084] The epoxy equivalent of the phenolic modified epoxy resin is 165 g / eq;

[0085] The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 1:1.

[0086] Example 7

[0087] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 1 comprises the following steps:

[0088] ① Preparation of component A: 8 kg of organic titanium modified epoxy resin, 8 kg of phenolic modified epoxy resin, 3 kg of Qishi toughening agent, and 0.5 kg of phthalate coupling agent NDZ-109 were added to a planetary mixer and mixed evenly. 2 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added and stirred for 15 minutes. After mixing evenly, 20 kg of quartz powder and 10 kg of glass flakes were added and stirred for 80 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0089] ② Preparation of component B: Add 5kg of amine curing agent, 0.1kg of curing accelerator, and 0.1kg of silane coupling agent KH-792 into a planetary mixer, stir for 15 minutes, then add 8kg of quartz powder, 8kg of glass flakes, 1kg of polyamide wax thixotropic agent, and 0.001kg of iron chrome black, and continue to mix and stir for 80 minutes. After mixing evenly, evacuate the materials in the planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste;

[0090] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0091] Example 8

[0092] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 2 comprises the following steps:

[0093] ① Preparation of component A: 12 kg of organic titanium modified epoxy resin, 12 kg of phenolic modified epoxy resin, 4 kg of Qishi toughening agent, and 1 kg of phthalate coupling agent TM-3 were added to a planetary mixer and mixed evenly. 4 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added thereto and stirred for 20 minutes. After mixing evenly, 30 kg of quartz powder and 20 kg of glass flakes were added thereto and stirred for 80 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0094] ② Preparation of component B: 10 kg of amine curing agent, 0.5 kg of curing accelerator, and 0.5 kg of silane coupling agent KH-602 were added to a planetary mixer, stirred for 20 minutes, and then 15 kg of quartz powder, 15 kg of glass flakes, 2 kg of thixotropic agent polyamide wax, and 0.001 kg of iron chrome black were added thereto, and the mixture was mixed and stirred for 100 minutes. After mixing, the materials in the planetary mixer were vacuumed to remove bubbles, and the mixture was packaged and stored to obtain component B, which was a black paste;

[0095] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0096] Example 9

[0097] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 3 comprises the following steps:

[0098] ① Preparation of component A: 9 kg of organic titanium modified epoxy resin, 11 kg of phenolic modified epoxy resin, 3.2 kg of Qishi toughening agent, and 0.6 kg of phthalate coupling agent NDZ-201 were added to a planetary mixer and mixed evenly. 2.5 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added thereto and stirred for 16 minutes. After mixing evenly, 22 kg of quartz powder and 15 kg of glass flakes were added thereto and stirred for 85 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0099] ② Preparation of component B: Add 6kg of amine curing agent, 0.2kg of curing accelerator, and 0.4kg of silane coupling agent A-1160 into a planetary mixer, stir for 20 minutes, add 9kg of quartz powder, 1ckg of glass flakes, 1.4kg of thixotropic agent polyamide wax, and 0.001kg of iron chrome black, continue to mix and stir for 85 minutes, and after mixing evenly, evacuate the materials in the planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste;

[0100] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0101] Example 10

[0102] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 4 comprises the following steps:

[0103] ① Preparation of component A: 10 kg of organic titanium modified epoxy resin, 10 kg of phenolic modified epoxy resin, 3.6 kg of Qishi toughening agent, and 0.9 kg of phthalate coupling agent NDZ-201 were added to a planetary mixer and mixed evenly. 3.8 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added thereto and stirred for 18 minutes. After mixing evenly, 28 kg of quartz powder and 18 kg of glass flakes were added thereto and stirred for 90 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0104] ② Preparation of component B: 9 kg of amine curing agent, 0.4 kg of curing accelerator, and 0.2 kg of silane coupling agent A-1160 were added to a planetary mixer, stirred for 16 minutes, and then 11 kg of quartz powder, 9 kg of glass flakes, 1.2 kg of thixotropic agent polyamide wax, and 0.001 kg of iron chrome black were added thereto, and the mixture was mixed and stirred for 95 minutes. After mixing, the materials in the planetary mixer were vacuumed to remove bubbles, and the mixture was packaged and stored to obtain component B, which was a black paste;

[0105] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0106] Embodiment 11

[0107] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 5 comprises the following steps:

[0108] ① Preparation of component A: 11 kg of organic titanium modified epoxy resin, 9 kg of phenolic modified epoxy resin, 3.4 kg of Qishi toughening agent, and 0.9 kg of phthalate coupling agent NDZ-201 were added to a planetary mixer and mixed evenly. 2.8 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added thereto and stirred for 16 minutes. After mixing evenly, 24 kg of quartz powder and 16 kg of glass flakes were added thereto and stirred for 90 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0109] ② Preparation of component B: Add 7kg of amine curing agent, 0.4kg of curing accelerator, and 0.3kg of silane coupling agent A-1160 into a planetary mixer, stir for 15 minutes, add 9kg of quartz powder, 14kg of glass flakes, 1.5kg of thixotropic agent polyamide wax, and 0.001kg of iron chrome black, continue to mix and stir for 90 minutes, and after mixing evenly, evacuate the materials in the planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste;

[0110] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0111] Example 12

[0112] The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive described in Example 6 comprises the following steps:

[0113] ① Preparation of component A: 10 kg of organic titanium modified epoxy resin, 10 kg of phenolic modified epoxy resin, 3.5 kg of Qishi toughening agent, and 0.8 kg of phthalate coupling agent NDZ-201 were added to a planetary mixer and mixed evenly. 3 kg of thixotropic agent (hydrophobic fumed silica whose surface was treated with titanate coupling agent) was added thereto and stirred for 18 minutes. After mixing evenly, 25 kg of quartz powder and 15 kg of glass flakes were added thereto and stirred for 85 minutes. After mixing evenly, the materials in the planetary mixer were evacuated to remove bubbles, and packaged and stored to obtain component A, which was a white paste;

[0114] ② Preparation of component B: Add 8kg of amine curing agent, 0.3kg of curing accelerator, and 0.3kg of silane coupling agent A-1160 into a planetary mixer, stir for 15 minutes, then add 12kg of quartz powder, 12kg of glass flakes, 1.5kg of thixotropic agent polyamide wax, and 0.001kg of iron chrome black, and continue to mix and stir for 85 minutes. After mixing evenly, evacuate the materials in the planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste;

[0115] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

[0116] The state of the high-strength, weather-resistant bridge segment assembly adhesive component A and component B after mixing is as follows: Figure 1 As shown, the color is similar to that of cement building materials. The iron chrome black component in component B can not only verify whether components A and B are mixed evenly, but also has excellent chemical resistance, outdoor durability, light resistance, high temperature resistance, environmental protection, non-toxicity, no color bleeding, no migration, and is one of the few black pigments with excellent infrared reflection function. After adding, the adhesive has good weather resistance.

[0117] The performance of the high-strength, weather-resistant bridge segment assembly adhesive obtained in Examples 7 to 12 was tested. The testing steps or standards and technical requirements are shown in Table 1, and the results are shown in Table 2.

[0118] Table 1 Performance test steps and technical requirements of high-strength and weather-resistant bridge segment assembly adhesive obtained in Examples 7 to 12

[0119]

[0120]

[0121] ① Time for glue application

[0122] Before the test, the test materials and apparatus should be placed at 25℃ for no less than 24h, and the component samples should be fully mixed at this temperature. Take out (100±5)g of the mixed sample and put it into a cylindrical insulated container with an inner diameter of 40mm. The thermal conductivity of the insulated container should not be greater than 0.20w / (m·k). Place the thermometer at the center of the sample. Start timing from the completion of sample mixing, and end when the temperature rises to 40℃ after mixing or obvious hardening occurs; the test result should be the arithmetic mean of 3 tests and be accurate to minutes.

[0123] ② Bonding time

[0124] Before the test, the test materials and instruments should be placed at 25℃ for no less than 24h. Immediately apply the mixed sample to the concrete specimen and start timing. After a certain period of air-drying, the concrete specimens are connected in pairs to conduct a concrete-to-concrete adhesion and bending test. After the two pieces of concrete are bonded, a bending test is conducted. The concrete interface is destroyed and qualified. The longest air-drying time corresponding to the qualified test is the bonding time.

[0125] Table 2 Performance test results of high-strength and weather-resistant bridge segment assembly adhesive obtained in Examples 7 to 12

[0126]

[0127]

[0128] It can be seen from the results in Table 1 that the high-strength, weather-resistant bridge segment assembly adhesive of the present invention shows excellent performance in the operability time, strength growth rate and weather resistance experiments, especially outstanding weather resistance, and can maintain high strength and durability in various complex external environments and climate changes, and is suitable for application in the construction of prefabricated splicing of bridge segments.

Claims

1. A high-strength, weather-resistant bridge segment assembly adhesive, characterized by: It is composed of component A and component B in a mass ratio of 2:1; in parts by weight, the component A is composed of the following raw materials: 8-12 parts of organic titanium modified epoxy resin, 8-12 parts of phenolic modified epoxy resin, 3-4 parts of Qishi toughening agent, 0.5-1 part of phthalate coupling agent, 20-30 parts of first quartz powder, 10-20 parts of first glass flakes and 2-4 parts of first thixotropic agent; the component B is composed of the following raw materials: 5-10 parts of amine curing agent, 0.1-0.5 parts of curing accelerator, 0.1-0.5 parts of silane coupling agent, 8-15 parts of second quartz powder, 8-15 parts of second glass flakes, 1-2 parts of second thixotropic agent and 0.001 parts of iron chrome black; The epoxy equivalent of the organic titanium modified epoxy resin is 312 to 333 g / eq; The epoxy equivalent of the phenolic modified epoxy resin is 160 to 170 g / eq.

2. The high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The organic titanium modified epoxy resin is prepared according to the following steps: Add epoxy resin E-51 into a reaction kettle, start stirring and heat to 130-140°C, add tetrabutyl titanate dropwise while stirring, keep warm and react for 2-3 hours after the addition is complete, remove by-products and low-boiling substances by distillation under reduced pressure, and obtain an organic titanium-modified epoxy resin with an epoxy equivalent of 312-333 g / eq; The mass ratio of the epoxy resin E-51 to tetrabutyl titanate is 185-206:26-28.

3. The high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The viscosity of the Qishi toughening agent is 50-500 mPa·S.

4. The high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The titanate coupling agent is NDZ-201; the silane coupling agent is A-1160.

5. The high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The amine curing agent is obtained by mixing aromatic amine condensate 105 and polyamide WSCM-4126 in a mass ratio of 3-5:5-7.

6. The high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The first thixotropic agent is hydrophobic fumed silica whose surface is treated with a titanate coupling agent; and the second thixotropic agent is polyamide wax.

7. The method for preparing the high-strength, weather-resistant bridge segment assembly adhesive according to claim 1, characterized in that: The following steps are involved: ① Preparation of component A: In parts by weight, add 8-12 parts of organic titanium modified epoxy resin, 8-12 parts of phenolic modified epoxy resin, 3-4 parts of Qishi toughening agent, and 0.5-1 part of phthalate coupling agent to the first planetary mixer, mix evenly, add 2-4 parts of the first thixotropic agent thereto and continue stirring for 15-20 minutes, add 20-30 parts of the first quartz powder and 10-20 parts of the first glass flakes thereto after mixing evenly, continue stirring for 80-100 minutes, and after mixing evenly, evacuate the materials in the first planetary mixer to remove bubbles, package and store to obtain component A, which is a white paste; The epoxy equivalent of the organic titanium modified epoxy resin is 312 to 333 g / eq; The epoxy equivalent of the phenolic modified epoxy resin is 160 to 170 g / eq; ② Preparation of component B: Add 5-10 parts of amine curing agent, 0.1-0.5 parts of curing accelerator, and 0.1-0.5 parts of silane coupling agent to the second planetary mixer, stir and mix, add 8-15 parts of second quartz powder, 8-15 parts of second glass flakes, 1-2 parts of second thixotropic agent and 0.001 parts of iron chrome black, continue to mix and stir for 80-100 minutes, after mixing evenly, evacuate the materials in the second planetary mixer to remove bubbles, package and store to obtain component B, which is a black paste; ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a mass ratio of 2:1 to obtain a high-strength, weather-resistant bridge segment assembly adhesive.

Citation Information

Cited By

  • Alicyclic polyamine curing agent, preparation method thereof and high-performance prefabricated part epoxy splicing adhesive

    CN122036531A